Role of the Opportunity Cost in the Overall Economic Development: Applied Study in The General Company for Leather Industries (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research set to indicate the role of the opportunity cost in the overall economic development (human and social development) by selecting the most appropriate alternative for the growth of the country in exchange for sacrificing profit limits to achieve this growth and development of the country, especially in the present circumstances of the country and after studying the reality of the economic case for him, as the problem lies with don't selecting the best alternative that enhances the gross domestic product, which extends to promote overall economic development and revive the industrial and agricultural sectors, productivity is more like Impotent, versus sacrifice alternative consumption may bring more financially lucrative than choose an alternative import from Foreign origin. The research has come to the set of results is the most important benefit that the sample company not to the promotion of agricultural and industrial production and the development of the local economy of the country as a result of the sacrifice of material profit larger than they would achieve a profit of content of human development through which the country is recovering and growth of the economy